2016
DOI: 10.1017/s0714980816000568
|View full text |Cite
|
Sign up to set email alerts
|

Primary Health Care Providers’ Perspectives: Facilitating Older Patients’ Access to Community Support Services

Abstract: The purpose of this paper is to understand how non-physician health care professionals working in Canadian primary health care settings facilitate older persons' access to community support services (CSSs). The use of CSSs has positive impacts for clients, yet they are underused due to lack of awareness. Using a qualitative description approach, 20 health care professionals from various disciplines and primary health care models were interviewed about the processes they use to link older patients to CSSs. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…Some nursing students brought community health and social service information to the huddle, but uptake was low. This finding is supported in the literature ( Ploeg et al., 2016 ). These implementation challenges demonstrate how complicated it is to execute experiential placements that cross boundaries among primary care, community-based care, and older adult care.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some nursing students brought community health and social service information to the huddle, but uptake was low. This finding is supported in the literature ( Ploeg et al., 2016 ). These implementation challenges demonstrate how complicated it is to execute experiential placements that cross boundaries among primary care, community-based care, and older adult care.…”
Section: Discussionsupporting
confidence: 91%
“…The precise nature of this complexity is a component of what we thought would be valuable for students to participate in this placement. Research has shown that primary care physicians rely on consults with the health-care team to create community linkages, family members to make connections, and patient self-referrals ( Ploeg et al., 2017 ). Strategies that may improve communication and trust between community-based health and social care sectors include obtaining endorsements from patients on community services, relying on staff with previous community experiences, sharing consultation notes, and delegating a team member for community outreach.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians tend to link with HSS by providing patients with community information, initiating linkages for those in need, and encouraging families to access services for their loved ones [34]. Our results identified strategies for primary care and CBHSS to build bridges to address the need-service gap for older adults including: a) using a person-focused approach; b) applying effective case coordination; c) adapting services to address access barriers or filling gaps; d) employing effective communication strategies between sectors; e) building trust and rapport between them; and (f) advocating for improved program access.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that physicians often relied on team members' knowledge and expertise, especially if they had delegated responsibility to link to outside resources [4]. In addition, primary care physicians experience challenges, such as insufficient time and staffing to link individuals with social services [38,39]. Interprofessional teams, practice nurses, and case managers have been shown to facilitate primary care and community linkages for older adults and others with long-term conditions, such as social isolation [2,3,34,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Although there is a growing body of evidence about clinic-based interventions to facilitate community resource referrals for disease self-management and selfcare, [24][25][26] and large health systems are rapidly adopting community resource referral technologies, 27 little is known about small primary care practices' implementation of community resource referral strategies. 28,29 To address this gap, this study applies the Consolidated Framework for Implementation Research (CFIR) 30 to investigate practice facilitator perceptions and observations about CommunityRx-H3 implementation.…”
mentioning
confidence: 99%